Cara Desain Kemasan Produk Mempengaruhi Respons Kognitif dan Perilaku Konsumen - Mia Angeline (Bina Nusantara University, 2010)
For manufacturers, product packaging designs play an important role in influencing sales and function as a means of communicating the product or corporate image to its consumer. Article examined the influence of packaging design on consumers’ cognitive response and their behavioral responses. Cognitive response of a packaging design was assessed through five brand personality factors from selected products, while consumers’ behavioral response was assessed through a range of approach – avoidance behavior. Data were collected by survey questionnaires to Bina Nusantara college students who have recognized or tried the selected products before. The conclusion of this study is the more positive product packaging design influence, the greater the tendency of consumers to show approach behavior, and vice versa.